2017
DOI: 10.1177/0143831x17734296
|View full text |Cite
|
Sign up to set email alerts
|

Why is there resistance to works councils in Germany? An economic perspective

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
(133 reference statements)
0
22
0
Order By: Relevance
“…This cost comprises, for instance, the costs of becoming exposed as a works councilor, as many employers have reservations against works councils, as well as the costs of actively representing one’s colleagues’ interests and being personally responsible for the negotiation outcomes. For a recent discussion of the causes of employer resistance against the introduction of works council, see Mueller and Stegmaier (2020).…”
Section: Institutional Setting and Some Hypothesesmentioning
confidence: 99%
“…This cost comprises, for instance, the costs of becoming exposed as a works councilor, as many employers have reservations against works councils, as well as the costs of actively representing one’s colleagues’ interests and being personally responsible for the negotiation outcomes. For a recent discussion of the causes of employer resistance against the introduction of works council, see Mueller and Stegmaier (2020).…”
Section: Institutional Setting and Some Hypothesesmentioning
confidence: 99%
“…This constitutes important new theoretical predictions for the hypothesis how works councils and novel technologies might be associated. A widely held view among managers and employers' associations is that the presence of works councils counters economic activities and technological progress within establishments (Müller/Stegmaier 2017b;Hübler 2003). This argument draws upon the use of wide-ranging co-determination rights of works councils.…”
Section: Hypotheses For the Link Between Work Councils And The Implementioning
confidence: 99%
“…Although some earlier studies showed a negative link with profitability, Mueller (2011) attributes such results to the use of data on managerial opinions or impressions; using actual profit data, he shows that the link is, indeed, positive. Moreover, Müller and Stegmaier (2017) discerned a number of reasons for managerial resistance to works councils in Germany, such as entrepreneurial freedom and shorttermism, that are consistent with the endowment effect. Surveying the wider European terrain, Osterloh et al (2011:339) found that countries with 'far-reaching co-determination laws generally had better economic performance in terms of employment, labour productivity, research investment, and labour peace.'…”
Section: Implications Of the Endowment Effect For The Second Objectionmentioning
confidence: 78%